2019
DOI: 10.36547/be.2019.2.2.49-53
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Potential of L-Asparaginase From Bacillus Sp. In Vitro

Abstract: This study reports the cytotoxic potential of L-Asparaginase isolated from Bacillus sp. Bacillus sp. was isolated from local soil/water samples and identified by rapid plate assay and further confirmed by phenotypic characterization. Extracellular L- Asparaginase was isolated from broth culture of Bacillus sp.  and purified by ammonium sulfate precipitation, followed by dialysis and ion exchange and gel filtration chromatography techniques. The purified enzyme was used to study the in vitro cytotoxic potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…In vitro cytotoxicity of l ‐ASNase from Bacillus sp. against human cervical cancer cell lines has been reported, 34 which is similar to that of current study. The maximum cytotoxic activity of purified l ‐ASNase from Chaetomium sp.…”
Section: Discussionsupporting
confidence: 92%
“…In vitro cytotoxicity of l ‐ASNase from Bacillus sp. against human cervical cancer cell lines has been reported, 34 which is similar to that of current study. The maximum cytotoxic activity of purified l ‐ASNase from Chaetomium sp.…”
Section: Discussionsupporting
confidence: 92%
“…The purified L-asparaginase showed a dose-depended cytotoxic effect on HeLa cells 68 . On the other hand, D'Souza et al 69 reported that L-asparaginase showed a significant cytotoxic activity against MCF-7, HeLa, HepG-2 and 3T3L1 cell lines. However, Moharib 70 reported that L-asparaginase has higher cytotoxic activity against HepG-2 and HCT-116 than HeLa and MCF7 carcinoma cell lines.…”
Section: Sds-page and Determination Of Monomeric Molecular Weight Of mentioning
confidence: 99%
“…There are three types of fingerprint identification method: capacitive, optical, and ultrasonic [1][2][3]. Among these three methods, optical and ultrasonic fingerprint sensors located under the smartphone's display are being studied by increasing numbers of industrial and research groups because full-screen displays have gradually become the mainstream technology in this market [4][5][6].…”
Section: Introductionmentioning
confidence: 99%